Respuestas
Respuesta dada por:
6
a + b = 5
a * b = -84
En la 1ºª ecuación b = (5 - a) por lo que la 2ª ecuación quedaría:
a * (5 - a ) = -84
5a - a² = - 84
a² - 5a - 84 = 0
![a = \frac{5 +- \sqrt{25+336} }{2} a = \frac{5 +- \sqrt{25+336} }{2}](https://tex.z-dn.net/?f=a+%3D+%5Cfrac%7B5+%2B-+%5Csqrt%7B25%2B336%7D+%7D%7B2%7D+)
![a = \frac{5 +- \sqrt{361} }{2} a = \frac{5 +- \sqrt{361} }{2}](https://tex.z-dn.net/?f=a+%3D+%5Cfrac%7B5+%2B-+%5Csqrt%7B361%7D+%7D%7B2%7D+)
![a = \frac{5 +- 19 }{2} a = \frac{5 +- 19 }{2}](https://tex.z-dn.net/?f=a+%3D+%5Cfrac%7B5+%2B-+19+%7D%7B2%7D+)
a = (5 + 19) : 2 = 24 : 2 = 12
b = (5 - 19) : 2 = -14 : 2 = -7
Los números son 12 y -7
a * b = -84
En la 1ºª ecuación b = (5 - a) por lo que la 2ª ecuación quedaría:
a * (5 - a ) = -84
5a - a² = - 84
a² - 5a - 84 = 0
a = (5 + 19) : 2 = 24 : 2 = 12
b = (5 - 19) : 2 = -14 : 2 = -7
Los números son 12 y -7
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años